Innovations in Mental Health Treatment for Children : Embracing Technology for Better Outcomes - Hassan Khalid Zubair; Ali Zubair (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Mental health issues among children are increasingly being recognized as critical areas of concern. This paper explores how innovations in technology, such as digital therapy apps, virtual reality, and AI-based support systems, are revolutionizing mental health treatment for children. The study evaluates the effectiveness of these technologies in providing accessible, personalized, and stigma-free mental health support, with a focus on early intervention and long-term care.